2011
DOI: 10.1902/jop.2010.100344
|View full text |Cite
|
Sign up to set email alerts
|

New York State Ear, Nose, and Throat Specialists' Views on Pre–Sinus Lift Referral

Abstract: Within the limits of the study, an attempt is made to develop a preoperative protocol, and 63 responses from ENT specialists suggested that the majority (58.7%) would recommend a maxillary CT scan before a sinus-lift surgery. Their greatest concerns were a prior sinus surgery, severe sinus inflammation, nasal/sinus obstruction, and oroantral fistulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
0
19
0
3
Order By: Relevance
“…A substantial number of responders (40.1%) recommended that patients with sinonasal symptoms, such as nasal obstruction, nasal discharge, and reduced sense of smell, also be referred by to an otorhinolaryngologist (Cote et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial number of responders (40.1%) recommended that patients with sinonasal symptoms, such as nasal obstruction, nasal discharge, and reduced sense of smell, also be referred by to an otorhinolaryngologist (Cote et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…According to their results, the majority (58.7%) of responders recommended a maxillary CT scan before SFE and referral to an otorhinolaryngologist when there is an evidence of a pathologic maxillary sinus on CT scan. A substantial number of responders (40.1%) recommended that patients with sinonasal symptoms, such as nasal obstruction, nasal discharge, and reduced sense of smell, also be referred by to an otorhinolaryngologist (Cote et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…7,9 Patients with chronic sinusitis related to allergies are at higher risk of postoperative complications. 10 Therefore, it is highly recommended to control and resolve the symptoms prior to surgery, which can be done with steroids and antihistamines. It has been shown that chronic and subacute maxillary sinusitis developed in 1.3 and 4.5% of cases with sinus augmentation procedure respectively.…”
Section: 5005/jp-journals-10024-1947mentioning
confidence: 99%
“…Referral to ENT specialist is not necessary in cases with normal anatomy or symptom-free small benign polyps (≤0.7 cm) without any compromised sinus drainage. 10 It has been demonstrated that mild postoperative inflammatory reaction is the result of transient physiological expression of mucosal lining defense system and the sinus can return to preoperative homeostasis after the procedure. Intrinsic potential of the sinus mucosal lining to achieve its original normal homeostatic status after sinus augmentation procedure is known as sinus compliance.…”
Section: 5005/jp-journals-10024-1947mentioning
confidence: 99%
See 1 more Smart Citation